Mechanical Properties of Polypropylene/Multi Walled Carbon Nanotube Composites (Hungarian Journal of Industry and Chemistry, 2010)
Carbon nanotubes (CNTs) are promising additives for polymer composites due to their excellent special mechanical, electrical, and thermal properties. Polypropylene/multi walled carbon nanotube (PP/MWCNT) composites were produced in single and double screw extruders. The composites contained 0.5, 2, 3 and 5 wt% multi walled carbon nanotubes (MWCTN). For comparison, composites with carbon black as an additive instead of MWCNT have been made. The melt flow rate (MFR), flexural modulus, yield strength, tensile strength and heat deflection temperature (HDT) of the composites have been examined.